Diagnostic performance of serum exosomal miRNA-720 in hepatocellular carcinoma - Jeong Won Jang; Ji Min Kim; Hye Seon Kim; Jin Seoub Kim; Ji Won Han; Soon Kyu Lee; Heechul Nam; Pil Soo Sung; Si Hyun Bae; Jong Young Choi; Seung Kew Yoon (Korean Liver Cancer Association, 2022)
Background/Aim Hepatocellular carcinoma (HCC) is associated with poor prognosis, largely due to late detection. Highly accurate biomarkers are urgently needed to detect early-stage HCC. Our study aims to explore the diagnostic performance of serum exosomal microRNA (miR)-720 in HCC. Methods Exosomal miRNA was measured via quantitative real-time PCR. A correlation analysis of exosomal miR-720 and tumor or clinico-demographic data of patients with HCC was performed. The receiver operating characteristic (ROC) curve was used to assess the diagnostic capacity of serum exosomal miR-720 for HCC, in comparison with α-fetoprotein (AFP) and prothrombin induced by vitamin K absence or antagonist-II (PIVKA-II). Results MiR-720 was chosen as a potential HCC marker via miR microarray based on significant differential expression between tumor and non-tumor samples. Serum exosomal miR-720 was significantly upregulated in patients with HCC (n=114) versus other liver diseases (control, n=30), with a higher area under the ROC curve (AUC, 0.931) than the other markers. Particularly, serum exosomal miR-720 showed superior performance in diagnosing small HCC (<5 cm; AUC, 0.930) compared with AFP (AUC, 0.802) or PIVKA-II (AUC, 0.718). Exosomal miR-720 levels showed marginal correlation with tumor size. The proportion of elevated miR-720 also increased with intrahepatic tumor stage progression. Unlike AFP or PIVKA-II showing a significant correlation with aminotransferase levels, the exosomal miR-720 level was not affected by aminotransferase levels. Conclusions Serum exosomal miR-720 is an excellent biomarker for the diagnosis of HCC, with better performance than AFP or PIVKA-II. Its diagnostic utility is maintained even in small HCC and is unaffected by aminotransferase levels.